If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15d + -12d = 66 Combine like terms: 15d + -12d = 3d 3d = 66 Solving 3d = 66 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Divide each side by '3'. d = 22 Simplifying d = 22
| w-45=32 | | .75z-6=7 | | 32c=480 | | 4n+9=43 | | 37+8p=66+7p | | 14x-5=3+10x | | 16-9=x+4 | | 3/4(8n-4)=-2 | | 3(7-x)=6 | | b+2b=30 | | -r+2=-6 | | -x^2+5x-4= | | 7p+12=3p+11 | | .8s+.16=4.8 | | 5+x=26+2x | | (2a+3)(3a-1)=2 | | 3(7)-3=6 | | 1.6t-0.5=7.5 | | 8*w= | | 8x+15-31=0 | | 5m-2m+4=-2m+-15 | | s=.2(300-10(5)) | | t+58=78 | | 2c-4(c-5)=-3+2c+7 | | y=x^2-10x+15 | | 6x+34=4x+284 | | x-3=11-8 | | 0.8(x+2)=2.4-x | | (X-4)=18 | | -3+(-10)-(-10)+-2= | | 15+4x=-7 | | 3x-9y=27 |